Analysis of results of survey on disciplinary liability for use of athletes and methods prohibited from the perspective of contemporary challenges of sport - Nowak, Michał (Journal of Education, Health and Sport, 2017)
This paper concerns the analysis of disciplinary responsibility of sportsman for doping. Responsibility for doping has a constructive character of disciplinary, but in exceptional circumstances, the nature of legal liability under the Penal Code. The motive to carry out the research was doping of tennis player - Maria Sharapova and she used Meldonium. For the purpose of the article was carried out a survey of 580 people. The study showed that despite the fact, that the respondents are interested in sports and amateur practice, it is not exactly are aware of what is doping in sport, and what are the penalties for its use in professional sport. People negatively evaluate such sportsman as Sharapova and they want greater penalties for doping. The survey is an important exploration opinion on doping. Despite more and more serious cases of doping in the world, and still these subject is treated marginally and slowly becomes a real plague among sportsman. Non - approved substances that appear on the market, are becoming harder to detect, more and more dangerous for the sportsman.